Rapid-onset supraventricular tachycardia following clozapine initiation and its management with verapamil: a case report - Alwabili, Afnan A. (International Journal of Advances in Medicine, 2019)
Clozapine is the drug of choice for treatment-resistant schizophrenia. However, the use of clozapine is limited by its serious adverse effects, which often underlie its discontinuation. The cardiovascular side effects that raise safety concerns include tachycardia, myocarditis and cardiomyopathy. The development of clozapine-induced tachycardia is usually observed on higher dosage especially at early stages of treatment. Here, author presented the case of a patient with treatment-resistant schizophrenia who developed asymptotic supraventricular tachycardia despite low dose of clozapine at the second day of treatment. Additionally, author explored the possibility of clozapine re-challenge in combination with verapamil treatment.